Evaluation of the Performance of the University Information Systems: Case of Moroccan Universities - M. Ayoub Gacim, Pr. Hicham Drissi, Pr. Abdelwahed Namir (Journal of Information & Systems Management, 2020)
The purpose of this paper is to develop a conceptual model of university information systems performance measurement. To do this we resorted to the choice of 3E-3P model. This model proposes a development under the spectrum of the systemic approach. The objective is to provide a tool to decision-makers in order to understand the dynamics of performance measurement. The model is based on a logic of decomposition of the global performance into three partial performances. The measurement is carried out at each pillar individually using a multi-criteria approach (MACBETH), and subsequently the consolidation of the three partial performances is carried out with the same multicriteria logic.